Medium of instruction and its effect on matriculation examination results for 2000, in Western Cape secondary schools : a study of examination results in relation to home language and language medium - October, Michellé (Centre for Applied Language and Literacy Studies and Services in Africa, 2015)
Bibliography: leaves 102-104.